Platelet-rich plasma injections for carpal tunnel syndrome: a systematic and comprehensive review. - Malahias, Michael-Alexander; Chytas, Dimitrios; Mavrogenis, Andreas F; Nikolaou, Vasilios S; Johnson, Elizabeth O; Babis, George C (Eur J Orthop Surg Traumatol, 2019)
A series of clinical trials focused on the use of ultrasound-guided platelet-rich plasma (PRP) infusions for the treatment of patients with carpal tunnel syndrome (CTS) were published over the last few years. However, the role of PRP for CTS remains unclear. We performed a systematic review according to Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. Two reviewers independently conducted the search using multiple databases: MEDLINE/PubMed, SCOPUS, Cochrane Database, and Web of Science. These databases were searched using terms "platelet" AND "rich" AND "plasma" AND "carpal" AND "tunnel". To maximize the search, backward chaining of references from retrieved papers was also undertaken. From the initial 19 studies, only five met our eligibility criteria. These articles included one randomized controlled double-blind study, one randomized controlled single-blind study, one randomized controlled non-blind study, one case-control study, and one case report. The vast majority of the included studies supported that PRP infusion improved the clinical condition of the patients and that PRP infusion was beneficial for patients with mild-to-moderate CTS. Therefore, PRP seems to be an interesting alternative for the treatment of mild-to-moderate CTS which, still, has not been thoroughly investigated. However, despite the promising results of the present studies, PRP has to be further tested before we reach to a definite conclusion regarding its therapeutic value.
Keywords: Carpal Tunnel Syndrome; Humans; Neural Conduction; Pain Measurement; Platelet-Rich Plasma